Peramalan Produksi Gula Menggunakan Metode Jaringan Syaraf Tiruan Backpropagation Pada PG Candi Baru Sidoarjo - Adi Sukarno Rachman; Imam Cholissodin; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sugar is a staple that is routinely used by the people of Indonesia. Sugar is often used in the food and beverage industry, food processing and preservation industries. Sugar needs increased supported by the lifestyle of Indonesian people, especially in daily life. PG Candi Baru is a sugar faktory that was built in 1832 and is a sugar-producing company SHS I (Superior Hooft Suiker) or White Crystal I (GKP). Since 2004 PG Candi Baru has greatly improved the company's performance and made changes through technological breakthroughs in the field of on farm and off farm. This research uses Artificial Neural Network backpropagation with network architecture design in the form of 4 input layer neurons, 3 hidden layers, and 1 output layer. Based on testing the maximum number of iterations obtained the lowest MAPE value of 17.85% with the number of iteration 800. And in the test of learning rate obtained the lowest MAPE value of 17.38% with the value of learning rate 0.4. If the maximum iteration value of 800 and the value of learning rate 0.4 will result in MAPE value of 16.98%.